Social Partnership as a Method of Legal Regulation of Employment Relations: The Case of Lithuania - Krasauskas Rytis; Mačernytė-Panomariovienė Ingrida (Baltic Journal of Law & Politics, 2022)
This article assesses the significance of social partnership in the regulation of employment relations. It is pointed out that the legal regulation of employment relations in Lithuania lacks stability, and the hypothesis is raised that this situation has been partly determined by the vanishing, negligible role of social partnership. The presumption is put forward that the regulation of employment relations can result in an effective and sustainable balance between the interests of employees and employers only if the possibilities of social partnership are used to their full extent and an optimal balance is achieved between contractual law-making and state law-making. The Lithuanian social partnership model is defined as gravitating from quasipartnership towards real social partnership; therefore, ways are still being sought as to how to strengthen the impact of social partnership on the regulation of employment relations by means of legislation and the use of soft law. To reveal the impact of social partnership on the regulation of employment relations in Lithuania, the article identifies and assesses the key indicators revealing the influence of social partnership on the regulation of employment relations and examines the positive legal regulation related to social partnership.